C-Terminal Binding Proteins Promote Neurogenesis and Oligodendrogenesis in the Subventricular Zone - Serra-Almeida, Catarina; Saraiva, Cláudia; Esteves, Marta; Ferreira, Raquel; Santos, Tiago; Cristóvão, Ana Clara; Bernardino, Liliana (Frontiers in Cell and Developmental Biology, 2021)
C-terminal Binding Proteins (CtBPs) are transcriptional modulators that can regulate gene expression through the recruitment of a corepressor complex composed of chromatin-modifying enzymes and transcriptional factors. In the brain, CtBPs have been described as regulators of cell proliferation, differentiation, and survival. Nevertheless, the role of CtBPs on postnatal neural stem cells (NSCs) fate is not known yet. Herein, we evaluate the expression and functions of CtBPs in postnatal NSCs from the subventricular zone (SVZ). We found that CtBPs were expressed in immature/progenitor cells, neurons and glial cells in the SVZ niche. Using the CtBPs modulator 4-methylthio 2-oxobutyric acid (MTOB), our results showed that 1 mM of MTOB induced cell death, while 5 µM, 25 µM and 50 µM increased the number of proliferating neuroblasts, mature neurons, and oligodendrocytes. Interestingly, it also increased the dendritic complexity of immature neurons. Altogether, our results highlight CtBPs putative application for brain regenerative applications.